PENGENDALIAN INTERNAL ATAS SIKLUS PENGELUARAN PADA SEBUAH PERUSAHAAN KONTRAKTOR DI INDONESIA - Fina Amaliah Hidayanti (Behavioral Accounting Journal, 2019)
This study aimed to evaluate the company's internal control implementation of expenditure cycle Standard Operating Procedure (SOP) PT. DWK. This study used an interpretive qualitative approach. This study found the lack of authorization on cash out evidence, disuse of temporary bon documents and drafts, and lack of management commitment in implementing SOP. The results of this study is to provide recommendations on the weaknesses of the implementation of SOP expenditure cycle of PT. DWK. By doing this research, misuse in the application of SOP expenditure cycle are expected can be minimized and prevented, so that the company's resources can be used effectively and efficiently.